Development of a screening score for Hemophagocytic Lymphohistiocytosis among pediatric patients with acute infection of Epstein-Barr virus - Li, Xun; Yan, Haipeng; Xiao, Zhenghui; Luo, Ting; Xie, Longlong; Yang, Yufan; Gong, Ling; Tang, Zhexuan; Huang, Jiaotian; Zhang, Xinping; Zheng, Mincui; Yao, Zhenya; et al. (Frontiers in Immunology, 2022)
Background and aims: Deciding when to suspect hemophagocytic lymphohistiocytosis (HLH) and perform diagnostic tests in patients with acute infection of Epstein-Barr virus (EBV) is challenging, given the high prevalence of EBV infection, the life-threatening risk of EBV-HLH, the relatively low incidence of EBV-HLH, and the wide spectrum of disease presentations. The aim of this study was to develop an EBV-HLH screening model for pediatric patients diagnosed with acute infection of EBV. Methods: An inpatient cohort with 3183 pediatric patients who were diagnosed with active infection of EBV was used to construct and validate the EBV-HLH screening score model. The model parameters were selected from common laboratory parameters using the method of Akaike Information Criterion-optimal selection through cross-validation under logistic regression. Performance of the score was evaluated and compared with the performance of screening methods using the number of cytopenias lineages. Results: The EBV-HLH screening score has five parameters, including hemoglobin, platelet, neutrophil, albumin, and lactate dehydrogenase. Using a cut-of value of 29, the scoring model had a sensitivity of 89.2% and a specificity of 89.5% in the validation set. The false negative rate, false positive rate, positive predictive value, and negative predictive value in the validation set was 10.8%, 10.5%, 26.8%, and 99.5%, respectively, similar to that of the training set. Conclusions: With five common laboratory parameters, the EBV-HLH score provides a simple tool to assist the identification of EBV patients who require further evaluation of HLH. Further studies are needed to evaluate the generalizability of the score and optimize the diagnose process for EBV-HLH.